Parkinson’s Law and an Ironic Rhetoric of Management - Sebestyén, Attila (Hungarian Journal of English and American Studies, 2022)
Cyril Northcote Parkinson, British historian, fiction writer, and, so to say, management guru, in Parkinson’s Law created his own successful way of critiquing organizational bureaucratization. Parkinson’s work falls under the Burkean category of “literature for use,” in which affectivity becomes guaranteed by the peculiarity of irony. As Wayne C. Booth suggested, even in the case of “stable irony” there may often be some possibility of further considerations (that is, the factor of uncertainty), despite all the efforts to rhetorically control this type of irony. Booth, however, also noted that a paradoxical situation may arise in which “unstable” irony, intended to be open-ended, becomes capable of creating possibilities for referential reading and practical application. Thus, Parkinson’s Law provides the duality of entertainment through its satire and the seriousness of its management thoughts (for instance, the relationship of work and time, work and headcount, workforce selection methods, and the extension of committees or departments). These two aspects, constantly intermingling, are examined through the rhetoric of irony working in Parkinson’s Law and the practical influences it may exert. (AS)